Synthesis and antimicrobial activities of some new 6-iodoquinazoline-based Schiff bases / Ahmed M Alafeefy ... [et al.] - M Alafeefy, Ahmed; Ashraf, Kamran; E Zain, Mohamed; Sultan, Sadia (Faculty of Pharmacy, 2024)
A library of thirteen new quinazoline-based Schiff bases was synthesized by simple, straightforward documented chemical procedures. Their skeletal structure was confirmed by IR, NMR, MS, and elemental analyses. The final compounds were also screened for their activities against eight selected microbial strains (two gram-positive and two gram-negative bacteria in addition to four fungal strains). Nine out of the thirteen tested compounds showed remarkable antimicrobial activities. However, six compounds, namely 7, 10, 13, 15, 16 and 18, showed antibacterial and antifungal activities, while compounds 9, 14 and 17 were devoid of antifungal and showed only antibacterial activities. The best activity was obtained by compounds 10 and 15, which were against Bacillus subtilis. The best MIC (1.90 µg/ml) and (3.9 µg/ml) were obtained by compound 10 against Bacillus subtilis and Staphylococcus aureus, respectively. Aspergillus fumigatus and Syncephalastrum racemosum were the most sensitive filamentous fungi, where compound 10 inhibited their growth at MIC (15.63 and 62.50 µg/ml), respectively.